Nucleotide polymorphism of udp-glucose dehydrogenase (udpgdh) from kelampayan (neolamarckia cadamba) - Ling, Siaw Ching. (University Malaysia Sarawak (UNIMAS), 2013)
Neolamarckia cadamba (Roxb.) Bosser, also known as Kelampayan, is a medium to large sized, fast growing tree that is belongs to the family of Rubiaceae. Kelampayan is used for industrial plantation and reforestation. It gives the best raw materials for plywood industry as well as pulp and paper industry. UDP-glucose dehydrogenase is an enzyme that catalyzes the conversion of UDP-glucose to UDP-glucuronate, which acts as a key precursor for the synthesis of hemicellulose and pectin in a multistep non-reversible reaction. Hemicellulose and pectin are the important components for cell wall formation. The main objective of this study was to identify nucleotide polymorphisms caused by single nucleotide polymorphisms (SNP) in UDPglucose dehydrogenase gene in Kelampayan. In order to do this, DNA extracted from five Kelampayan trees were first subjected to polymerase chain reaction to obtain the desired UDPGDH sequence. BLASTn analysis was then performed to search for sequence homology. Five UDPGDH sequences were aligned using CLC Free Workbench 6.0 for SNP detection. A total of 3 SNP and 3 InDels had been detected in partial UDP-glucose dehydrogenase sequence. Apart from that, five restriction enzymes which include BssKI, PspGI, StyD4I and MspJI were also detected for three SNP sites.